Pengaruh Komitmen Pada Profesi Dan Dukungan Organisasional Terhadap Motivasi Berprestasi Dosen - Sudiyatmi, Titik . (WIDYATAMA, 2012)
Pengaruh Komitmen Pada Profesi Dan Dukungan Organisasional Terhadap Motivasi Berprestasi Dosen Titik Sudiatmi Program Studi Pendidikan Bahasa danSastra IndonesiaFakultas Keguruan dan Ilmu Pendidikan Universitas Veteran Bangun NusantaraSukoharjoJln.Letjen Sujono Humardani No 1 Sukoharjo 57521 Telp.(0271)593156 Fax (0271)591065 Abstract Lecturers has commitment with their profession will always participate in each scientific activities in their campus so it will influence for their achievement. Commitment is a value belief with the organization willingness which try to do the best for the important of the organization itself. The organization support influence significant for the motivation to achieve organization support better than a lecturer so it will predict that lecturer will more increasing the achievement motivation. In a University, the organization support is very important to create the organization climate so it is hoped that the lecturer will motivate to do the lecturer activities like teaching, research, and social perpetuation professional. Kata Kunci: Komitmen Pada Profesi, Dukungan Organisasional, Motivasi Berprestasi